Solar-powered flood early warning system with short message service (SMS) notifications - Nur Anis Athirah; N. H. Radzi; M. N. Abdullah; S. A. Jumaat; N. Z. Mohamad (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Flood is one of the most common hazards in Malaysia. Flood effects can be local, or very large, affecting the neighborhood or community and entire river basins. This flood develops slowly; sometimes over a period of days while sometimes develop quickly in just few minutes. With the real time flood information, it will allow public safety organizations and other emergency managers to effectively plan their resource deployment within the limited time of alert. Hence, this project aims to design the solar powered flood alert warning system by using solar energy as the power supply. This system will send message using GSM to the residents to notify them about the flood occurred. In this project, three LEDs were used to indicate the height of the water levels which are safe, alert and danger conditions. Each of the height have different water level that indicates the level of safety for each condition.